PERLINDUNGAN HUKUM TERHADAP PEKERJA AKIBAT PEMUTUSAN HUBUNGAN KERJA (PHK) DITINJAU DARI UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Ondang Surjana; Efa Laela Fakhriah2 Laela Fakhriah (Iustitia Omnibus (Jurnal Ilmu Hukum), 2021)
ABSTRACT Employment law regulates the relationship between workers and employers. The employment relationship occurs because of the employment agreement between the employer and the worker. The failure of the agreement resulting in the release of workers in the form of Termination of Employment, positioning workers as the more disadvantaged party, so that legal protection is needed for workers due to Termination of Work (PHK). The objectives of this study are: 1) to understand the legal protection of workers due to Termination of Employment (PHK) in terms of Law Number 13 of 2003 concerning Manpower, and 2) to find a mechanism for resolving disputes over Termination of Employment (PHK) between workers and companies. The research method uses a normative juridical research approach that examines and analyzes established labor law norms capable of providing legal protection for workers due to termination of employment (PHK). The conclusion of the research provides an understanding that the legal protection of workers due to termination of employment in terms of Law Number 13 of 2003 concerning Manpower is carried out by considering social, economic and legal aspects to provide legal certainty for workers and employers are required to comply with the rules given both warnings and sanctions. enforced to be implemented properly. The results of this study found that the settlement mechanism for termination of employment between workers and companies, in accordance with Law Number 13 of 2013 concerning Manpower, begins with Bipartite, if there is no agreement, it is continued with Tripartite in the form of mediation with the government represented by the City Manpower Office/ District, then if there is no agreement, proceed to the Industrial Relations Court for legal remedies in the employment relationship between the workers and employers. Keywords: Employment, Legal Protection, Workers, Termination of Employment